Citric Acid Induction and Statistical Optimization for Production Enhancement of Catalase by Serratia marcescens SYBC08 - Zeng, Hua-Wei; Cai, Yu-Jie; Liao, Xiang-Ru; Zhang, Feng; Li, Yu-Lin; Zhang, Da-Bing (Asian Journal of Chemistry, 2010)
The process of enhancing production of catalase by Serratia marcescens SYBC08 was carried out in submerged fermentation. Catalase production of critic acid induction was increased by 92 % compared to that of glucose. Statistical experimental designs were used in optimization of catalase production. Temperature, initial pH and corn steep liquor powder concentration were identified as the most significant factors by using Placket-Burman design. The optimum values of three significant factors were determined using central composite design and response surface analysis. While three optimum significant factors were revealed as temperature (32.8 °C), initial pH (5.9) and corn steep liquor powder concentration (33.8 g L-1), the maximum predicted catalase production of 11632.88 U mL-1 was calculated out using a two second-order polynomial equation. In a validate experiment, maximum catalase production of 12182.74 U mL-1 was achieved and had 28.27 % increasement compared to that under unoptimized conditions.